The effect of plastic waste on the coastal socio-economic community of the Lantebung in Makassar City, South Sulawesi Province, Indonesia - Lukman Daris; Andi Nur Apung; Wahyuti; Irwansyah (Hasanuddin University, 2022)
Mangrove ecosystems provide various ecological and economic functions, such as environmental services as an ecotourism area. This study aims to determine the factors that influence plastic waste on the socio-economic life of coastal communities in the Lantebung area. The data in this study are primary data obtained from interviews with respondents with structured questions and statements. The data collection method with structured interview and data analysis used in this research is an impressional statistical method with an SEM approach. The results of the data analysis, the factors that affect plastic waste are the volume of waste with a loading factor value of 0.966. In contrast, the factors that affect the social economy is a loading factor value of 0.732. Plastic waste has a significant relationship to the socio-economic community, with a P value of 0.018 less than 0.05. The direction of the relationship between plastic waste and the socio-economic community is negative, with -0.240, meaning that the higher the plastic waste, the socio-economic community in the Lantebung mangrove area will decrease.